Imidazole‐stabilized gold nanoparticles induce neuronal apoptosis: An in vitro and in vivo study. Issue 4 (2nd August 2014) - Imperatore, Roberta; Carotenuto, Gianfranco; Di Grazia, Maria Antonietta; Ferrandino, Ida; Palomba, Letizia; Mariotti, Raffaella; Vitale, Emilia; De Nicola, Sergio; Longo, Angela; Cristino, Luigia
Abstract Gold nanoparticles are increasingly being employed in innovative biological applications thanks to their advantages of material‐ and size‐dependent physics and chemical interactions with the cellular systems. On the other hand, growing concern has emerged on the toxicity which would render gold‐based nanoparticles harmful to cell cultures, animals, and humans. Emerging attention is focused on the interaction of gold nanoparticles with nervous system, especially regarding the ability to overcome the blood–brain barrier (BBB) which represents the major impediment to the delivery of therapeutics into the brain. We synthesized highly stable 2‐mercapto‐1‐methylimidazole‐stabilized gold‐nanoparticles (AuNPs)‐mmi to investigate their entry, accumulation, and toxicity in vitro (SH‐SY5Y human neuroblastoma cells) and in vivo (brain of C57BL/6 mice) through optical and electron microscopy. After incubation in the cell culture medium at the lowest dose of 0.1 mg/mL the (AuNPs)‐mmi nanoparticles were found compacted and recruited into endosome/lysosomes (1 h) before their fusion (2 h) and the onset of neuronal death by apoptosis (4 h) as proved by terminal‐transferase‐mediated dUTP nick end labeling assay and caspase‐3 immunoreactivity. The ability of (AuNPs)‐mmi to cross the BBB was assessed by injection in the caudal vein of C57BL/6 mice. Among different brain regions, the nanoparticles were found in the CaudatoPutamen area, mainly in the striatal neurons 4 h after injection. These neurons showed the typical hallmarks of apoptosis. Our findings provide, for the first time, the dynamic of 2‐mercapto‐1‐methylimidazole nanogold uptake. The molecular mechanism which underlies the nanogold‐driven apoptotic event is analyzed and discussed in order to take into account when designing nanomaterials to interface with biological structures. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1436–1446, 2015.